Sydnytt : Anders A. - Anette Abrahamsson - Björn Almviken - Simon Arne ... - Nilsson, Bo (Malmö : Malmö Konsthall, 1987)
Anders A. ; Abrahamsson, Anette ; Almviken, Björn ; Arne, Simon ; Arnesson, Peter ; Battista, Enrique ; Bendon, Paul Mitchell ; Bjershagen, Lotta A. ; Cesarec, Marko ; Dacke, Peter ; Ebers, Stina ; Ekholm, Lars ; Ericsson, Mikael ; Ewald, Johnny ; Forslund, Leonard ; Hahne, Peter ; Hydén, Acke ; Kappel, Anders ; Malmeström, Tamara ; Melin, Truls ; Orfali, Ingrid ; Pettersson, Bertil ; Ross, Björn ; Sternäng, Peter ; Svenbro, Annika ; Tallinger, Olle ; Theselius, Jonas ; Ylivallo, Tarja
Sydnytt, Malmö Konsthall, Malmö, 17 januari - 15 februari 1987
boek